1994
DOI: 10.1523/jneurosci.14-02-00576.1994
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of somatostatin with GABA or glutamate in distinct afferent terminals presynaptic to the Mauthner cell

Abstract: The presence of somatostatin in afferent fibers impinging on the goldfish Mauthner (M-) cell was determined using immunohistochemical methods, combined with confocal and electron microscopy, and the relationship of this peptide with inhibitory and excitatory terminals was studied. Somatostatin-reactive boutons were present only on the distal part of the M-cell's lateral dendrite. Somatostatin immunoreactivity was observed in typical large myelinated club endings (LMCEs) corresponding to mixed (electrical and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Four compartments were defined, the axon cap (AC), the soma outside the AC (S) and the medial (mLD) and distal (dLD) parts of the lateral dendrite (150-200 and 350-450 km away from the soma, respectively). We have chosen these sectors because the distributions of glycine-and GABAcontaining boutons are well-characterized on the soma and on the lateral dendrite (Korn et al, 1990;Petrov et al, 1991;Triller et al, 1993;Sur et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Four compartments were defined, the axon cap (AC), the soma outside the AC (S) and the medial (mLD) and distal (dLD) parts of the lateral dendrite (150-200 and 350-450 km away from the soma, respectively). We have chosen these sectors because the distributions of glycine-and GABAcontaining boutons are well-characterized on the soma and on the lateral dendrite (Korn et al, 1990;Petrov et al, 1991;Triller et al, 1993;Sur et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…In goldfish, for example, dopamine enhances the efficacy of excitatory synapses to the M-cell LD (Pereda et al 1992(Pereda et al , 1994. Also in goldfish, the neuropeptide somatostatin is colocalized with glutamatergic excitatory and GABAergic inhibitory synaptic contacts that impinge onto the M-cell, an arrangement suggesting a modulatory role for this neuropeptide (Sur et al 1994). Indeed, local application of somatostatin onto the M-cell LD increases excitatory synaptic transmission in the large club endings that provide auditory input to the cell (Pereda et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, our experiments cannot exclude the possibility that the larger PSPs in DOMs may be also mediated by modulating the efficacy of excitatory synaptic transmission at the mixed electrotonic and chemical junctions between the large eighth nerve endings and the M-cell (Pereda et al 1992(Pereda et al , 1994. For example, in goldfish, local application of the neuropeptide somatostatin onto the M-cell lateral dendrite increases excitatory synaptic transmission (Pereda et al 1997), and somatostatin has been shown to be co-localized with glutamatergic excitatory but also with GABAergic inhibitory synaptic contacts onto the M-cell (Sur et al 1994). These findings are interesting because somatostatin also controls social behavior in A. burtoni (Hofmann and Fernald 2000;Hofmann 2006, 2007) and thus constitutes one candidate for the proposed neuromodulatory link between social state and M-cell excitability.…”
Section: Discussionmentioning
confidence: 99%